1990
DOI: 10.1111/j.1365-2605.1990.tb01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive oxygen species in subgroups of infertile men

Abstract: The capacity to generate reactive oxygen species (ROS), both basally and after stimulation with the calcium ionophore A23187, was examined in the motile fraction of sperm isolated after swim-up from the semen of 10 naturally fertile men and three groups of infertile patients. The latter included: (1) men with a non-bacterial inflammation of the genital tract (n = 10); (2) men unable to impregnate their partners during an intra-uterine insemination programme (IUI) (n = 8) and their matched controls (n = 6); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The same pathologies induce many biological and clinical effects, such as modifications in microcirculation, venous stasis and subsequent hypoxia, leucocyte activation and cell necrosis, all of which increase ROS in the semen. In fact, studies have shown radical oxygen species to be higher in the male partner of infertile couples suffering from selected andrological conditions (97,99,102). Particular attention has been given to the harmful effects of ROS on in vitro spermatozoa and the implications of this in semen preparation in In Vitro Fertilization (IVF) programs.…”
Section: Seminal Fluid and Ros Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The same pathologies induce many biological and clinical effects, such as modifications in microcirculation, venous stasis and subsequent hypoxia, leucocyte activation and cell necrosis, all of which increase ROS in the semen. In fact, studies have shown radical oxygen species to be higher in the male partner of infertile couples suffering from selected andrological conditions (97,99,102). Particular attention has been given to the harmful effects of ROS on in vitro spermatozoa and the implications of this in semen preparation in In Vitro Fertilization (IVF) programs.…”
Section: Seminal Fluid and Ros Damagementioning
confidence: 99%
“…The harmful impact of radicals and toxic compounds on sperm function has been well studied with particular emphasis on the negative effects of ROS on sperm function (96)(97)(98)(99). In mammalian cells the alteration of the fatty acid pattern of the membrane produces significant modifications including changes in the activity of different lipid-dependent enzymes and in the resistance to physical or chemical stress (100).…”
Section: Seminal Fluid and Ros Damagementioning
confidence: 99%
“…[11À13] In males, the most common aneuploidies diagnosable by cytogenetic analysis are Klinefelter syndrome (47, XXY), the (47, XYY) syndrome and de la Chapelle syndrome (46,XX male). In females, the most common aneuploidies that may affect fertility are Turner syndrome (45, X0) and its variants and the (46, XY) female syndrome.…”
Section: Basic and Extended Infertility Assessments: Pros And Consmentioning
confidence: 99%
“…Free radicals and reactive oxygen species may play a number of significant and diverse roles in reproductive biology. Free oxygen radicals have been shown to have adverse effects on sperm function [2,8,10,15,161, and it is hypothesized that human semen may contain an antioxidant defense system to protect the sperm from the free radical-induced damage [2, 8, 161. Our findings indicate that antioxidants are indeed present in human seminal plasma that can protect the sperm from ROS and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…These ROS could induce a state of oxidation stress for sperm cells through membrane lipid peroxidation, thus causing infertility [2,3,10,151.…”
mentioning
confidence: 99%